The impact of financial digitization on the develpoment of accounting information systems - Salam Hassan Ajeel Al-Magsoosi (Scholar Express Journals, 2025)
The study examines the importance of financial digitization as a key mechanism to raise the efficiency of accounting information systems
Keywords: financial; digitization; accounting